Ordbøker og folkelivsgransking (etnologi) - Myhren, Mange (Nordiske Studier i Leksikografi, 1995)
One of the fields interest for ethnology is the study of different aspects of labour: tools, equipment, and the work-process in its widest sense. Each field of work, each type of tool, and each method of operation has its own words or technical terms; and for the writer of dictionaries it is of importance to include lexical items, with appropriate semantic descriptions, from this field. The present paper focuses on the following topics: 1. A brief attempt at drawing a distinction between every day vocabulary and technical terminology (following Coseriu 1973). 2. Examples of how Ivar Aasen (1850, 1873 and 1925) handled vocabulary of this type, illustrated by words/technical terms grouped under the heading "tools", "house", and "cleanliness/cleaning". 3. Aasen’s lexical items and technical terms are compared to information from Norwegian ethnological literature, by Eilert Sundt, a contemporary with Aasen. 4. What can the writer of dictionaries Ieam from ethnological Iiterature?